Influence of severe double shot peening on microstructure properties of Ti 6Al-4V and Titanium Grade 2 dissimilar joints using laser beam welding. (March 2020) - Logesh, M.; Selvabharathi, R.; Thangeeswari, T.; Palani, S.
Highlights: Laser beam welding is used to dissimilar joint of Ti 6Al-4V and Titanium Grade 2 sheets. The severe double shot peening is the main parameter of improving the mechanical strength. Post peening process is improve weld quality, due to the α phase conversion into β1 /β2 phase. Abstract: The present investigation deals with the effect of Severe Double Shot Peening (SDSP) of Peening pre-weldment and Post peening weldment on microstructure properties of Ti 6Al-4V and Titanium Grade 2 dissimilar joint made by laser beam welding. Laser beam welding was performed for butt joint configuration. Full depth of penetration was obtained for the laser beam of 1200 W, welding speeds of 250 mm/min and focus distance of 8 mm configuration. Microstructure studies at weld zone and heat affected zone revealed the presence of more amounts of α martensite and B phases. Tensile study displayed that all the failures occurred at the weld zone in both Peening pre-weldment and Post peening weldment of SDSP. X-rays Diffraction analysis showed the slight presence of residual stress in the Post peening weldment of SDSP. Average hardness value of both dissimilar material reached 285 HV. While comparing the hardness at heat affected zone and welded zone, the hardness of welded zone gradually decreased owing to the failure of conversion of α phase into β1 /β2 phase. SEM image exhibited the depth of Peening pre-weldment and Post peening weldment weldments of 8 µm and 10 µm respectively which led to the enhancement of hardness value. Further, the coarse grain boundaries, O-phases and α/α′ phases were observed in the heat affected zone. Fracture morphology of tensile samples revealed the inner minor cracks and voids at fusion zone. Moreover, the formation of Cr2 N and CrN was not observed in both welded and heat affected zone that improved the better tensile and bending strength.